Formulation and evaluation of oil entrapped floating beads of Piperine for peptic ulcers - Madhavi, B. Bindu; Ramalingam, R.; Nath, A. Ravinder; Banji, David (Pharmacognosy Communications)
Background: Peptic ulcers remain a challenge for identifying more effective and safer anti-ulcer therapies. Over the last few decades herbs have become the major source for the treatment of various diseases. The common spice piperine has shown a significant role in healing peptic ulcers. A fatty diet including olive oil has also proved effective for its anti ulcer activity. Objective: A formulation of floating piperine beads with the olive oil entrapment, to reside in the gastric environment, was tested for its therapeutic value. Materials and Methods: Floating beads were prepared by the ionic gellation method, followed by air drying. Results: The prepared beads showed entrapment efficiency in the range of 75-85% with flotation for more than 12 hours. The inclusion of HPMC prolonged the drug release up to 12 hours. Conclusion: From the results it can be concluded that piperine in the form of olive oil entrapped floating beads is beneficial in treating peptic ulcers because of its longer residence time at the site of action and also because of the additive anti-secretary activity of the oil.
Keywords: Anti ulcer activity; floating beads; Hydroxy Propyl Methyl Cellulose; olive oil; piperine